THE PROBLEMS OF TEACHING OF LINGUISTIC AND CULTURAL REALIA - Adambayeva Nafisa, Mirzaxmedova Gulmira Salimjonovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article explores the challenges in teaching linguistic and cultural realia to language learners. It highlights the complexity of conveying culturally bound concepts that often lack direct equivalents in other languages. The article also examines effective strategies and tools to overcome these challenges, emphasizing the importance of integrating both linguistic and cultural elements in language education.